Sufi Master and Qur’an Scholar: Abū’l-Qāsim al-Qushayrī and the Latā’if al-Ishārāt By Martin Tran Nguyen (Oxford: Oxford University Press in association with the Institute of Ismaili Studies Qur’anic Studies Series, 2012. 303 pages.) (American Journal of Islam and Society, 2015)
Over the past few years, an increasing number of academic publications havefocused on the life and work of the Sufi master and theologian Abū l-Qāsim‘Abd al-Karīm b. Hawāzim al-Qushayrī (d. 465/1072 in Nishapur). While thisincreased interest has filled in many gaps in our understanding of this man,an important figure for the Islamic mystical tradition, Nguyen’s monographrepresents the first in-depth inquiry into Qushayrī and his doctrine.Nguyen’s book, developed from his doctoral dissertation, concentrates onthe Laṭā’if al-Ishārāt (hereafter LI), typically considered a mystical exegeticaltreatise but which Nguyen shows should be seen in a broader and more nuancedlight. He analyzes the text through the concept of “tradition,” reading it as theresult of a network of different cultural and spiritual influences. Their unificationin this exegetical treatise can be considered Qushayrī’s main achievement. Assuch, Nguyen’s work represents a major contribution in the fields of Qur’anicand Sufi studies as well as the broader field of medieval intellectual history.The book’s nine chapters cover the following subjects: In the introductionthe author positions the LI vis-à-vis the different exegetical traditions (juridical,encyclopedic, and theological), arguing that it belongs to what Walid A.Saleh calls the “Nishapuri school” of exegesis. Thus, as Nguyen points out,Qushayrī’s Tafsīr is “located and contextualized onto a number of differentbut overlapping historical axes” (p. 16) ...